Itaconate / conjugated diene / terpene multicomponent bio-based rubber and vulcanizates thereof and methods of making
By employing redox emulsion polymerization technology for itaconic acid esters, conjugated dienes, and terpenes in a multi-component copolymer bio-based rubber, the problems of high cost and insufficient performance of existing bio-based rubbers have been solved. This technology produces a rubber with high bio-based content and excellent mechanical properties, suitable for industrial applications.
Patent Information
- Application Number
- CN202310885386.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2043-07-18
AI Technical Summary
The existing preparation process for bio-based rubber is costly, and the mechanical and overall properties of bio-based rubber need to be improved, especially in tire applications.
Bio-based rubber with high bio-based content and excellent mechanical properties was prepared by using itaconic acid ester, conjugated diene and terpene multi-component copolymer bio-based rubber through redox emulsion polymerization technology. By combining specific component ratios and process conditions, a bio-based rubber was prepared.
This study achieves high biomass content and excellent mechanical properties in bio-based rubber, making it suitable for industrial applications, reducing preparation costs, and improving the dynamic mechanical properties and anti-slip properties of the material.
Smart Images

Figure CN119331169B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber synthesis technology, and more specifically, to an itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, its vulcanizate, and its preparation method. Background Technology
[0002] Due to concerns about ecological balance and sustainable economy, various types of bio-based synthetic elastomers have been developed in recent years, including bio-based isoprene rubber, bio-based ethylene propylene rubber, and bio-based butadiene rubber. The preparation process of these bio-based rubbers typically involves first converting biomass into traditional monomers, and then polymerizing them using traditional methods, which results in higher costs.
[0003] The applicant disclosed high molecular weight isoprene-based itaconic acid ester rubber in "A method for preparing itaconic acid ester / isoprene copolymer type bioengineering rubber raw rubber by low temperature emulsion polymerization" (CN102558437A); and disclosed butadiene-based itaconic acid ester rubber with better comprehensive performance in "An itaconic acid ester / butadiene copolymer type bio-based engineering rubber and its preparation method" (CN104945817A).
[0004] Terpenes are olefinic compounds whose molecular formula is an integer multiple of isoprene. They are a class of naturally occurring hydrocarbons widely found in plants, particularly conifers. They are the main components of resins and turpentine, a resin-derived oil. Recent studies have shown that in addition to abundant terpenes in plants, a large number of terpenes have also been extracted from marine organisms; the total number of known terpenes exceeds 22,000. Many terpenes can participate in copolymerization to prepare novel bio-based polymers, but their use is often limited by performance constraints. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, its vulcanizate, and a preparation method thereof. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber of this invention not only has a high bio-based content but also exhibits excellent mechanical properties and comprehensive performance in tire applications.
[0006] One objective of this invention is to provide an itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, wherein the structural formula of the bio-based rubber is:
[0007]
[0008] n' is 1-5, and R1 and R2 are hydrogen atoms or carbon atoms. 1~20Alkyl group, a+b=1~90%, n=1~99%, x+y+z=1~95%, p=0~30%, X1 is a hydrogen atom or methyl group, X2 is a functional group structure containing at least one of epoxy group, carboxyl group, hydroxyl group or amide group, wherein R1 and R2 are the same or different;
[0009] Preferably, n' is 2 or 3, and R1 is hydrogen or C. 1-10 Alkyl group, where R2 is hydrogen or C 1-10 Alkyl groups, a+b = 5-70%, n = 10-90%, x+y+z = 5-90%, p = 0-10%.
[0010] In a preferred embodiment of the above technical solution, the epoxidized itaconic acid ester / butadiene / myrcene bio-based rubber has the following structure:
[0011]
[0012] In another preferred embodiment of the above technical solution, the epoxidized itaconic acid ester / butadiene / farnese bio-based rubber has the following structure:
[0013]
[0014] In the bio-based rubber, the structural units derived from itaconic acid esters account for 1-99% by mass in the copolymer, preferably 10-90%.
[0015] Preferably, the number-average molecular weight (Mn) of the bio-based rubber is 50,000-1,000,000, more preferably 100,000-800,000; and the molecular weight distribution (Mw / Mn) is 1.5-10.0, more preferably 2.0-5.0. When the molecular weight and molecular weight distribution reach the above values, it can ensure that the composite material has sufficient mechanical properties and good processing performance, making it suitable for industrial applications.
[0016] Preferably, the bio-based rubber is obtained by copolymerizing raw materials comprising the following components:
[0017] Each component, by weight:
[0018] Based on a total weight of 100 parts by weight of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer:
[0019] The mass ratio of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer is (0.14–18):(0.07–18):1;
[0020] 0-30 parts by weight of functionalized monomers;
[0021] 100-300 parts by weight of deionized water;
[0022] Emulsifier 0.1-15 parts by weight;
[0023] Electrolyte 0.1-3 parts by weight;
[0024] Activator: 0.01-0.2 parts by weight;
[0025] Chain transfer agent 0.01-0.4 parts by weight;
[0026] Initiator 0.01-5 parts by weight;
[0027] The amount of flocculant used is 20-60 wt% of the total weight of the copolymer latex after polymerization.
[0028] Preferably, the components are expressed in parts by weight as follows:
[0029] Based on a total weight of 100 parts by weight of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer:
[0030] The mass ratio of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer is (0.16–16):(0.08–16):1;
[0031] Functionalized monomers: 0-10 parts by weight;
[0032] 150-250 parts by weight of deionized water;
[0033] Emulsifier 2-10 parts by weight;
[0034] Electrolyte 0.1-1.5 parts by weight;
[0035] Activator: 0.02-0.1 parts by weight;
[0036] Chain transfer agent 0.03-0.25 parts by weight;
[0037] Initiator 0.02-2 parts by weight;
[0038] The amount of flocculant used is 30-50 wt% of the total weight of the copolymer latex after polymerization.
[0039] Preferably, the structural formula of the itaconic acid ester monomer is:
[0040]
[0041] R1 and R2 are hydrogen atoms or C atoms. 1~20 Alkyl groups, wherein R1 and R2 may be the same or different; R1 is preferably hydrogen or C. 1-10 The alkyl group, R2 is preferably hydrogen or C 1-10 Alkyl groups;
[0042] Preferably, the itaconic acid ester monomer is at least one selected from dimethyl itaconic acid, monomethyl itaconic acid, diethyl itaconic acid, monoethyl itaconic acid, dipropyl itaconic acid, monopropyl itaconic acid, dibutyl itaconic acid, monobutyl itaconic acid, dipentyl itaconic acid, monopentyl itaconic acid, dihexyl itaconic acid, diheptyl itaconic acid, monoheptyl itaconic acid, dioctyl itaconic acid, monooctyl itaconic acid, dinonyl itaconic acid, monononyl itaconic acid, didecyl itaconic acid, and monodecyl itaconic acid; and / or,
[0043] The conjugated diene monomer is C n H 2n-2 At least one of the following, wherein n≥4, preferably at least one of C4H6 or C5H8, i.e., butadiene or isoprene; and / or,
[0044] The terpene monomer is (C5H8). n At least one of the following, wherein n≥1, preferably at least one of (C5H8)2 or (C5H8)3, i.e., myrcene, ocimene, and farnesene, which not only increases the biomass content in the bio-based rubber matrix, but also improves the dispersion of fillers due to the presence of long side groups; and / or,
[0045] The functionalized monomer is at least one selected from glycidyl methacrylate, methacrylic acid, hydroxyethyl methacrylate, acrylamide, and vinyl acetate. The functionalized monomer is a monomer with reactive functional groups. This monomer unit is intended to further enhance the interfacial interaction of the filler, improve filler dispersion, and thus optimize the dynamic mechanical properties of the material; and / or,
[0046] The emulsifier can be a commonly used emulsifier in the rubber industry, preferably at least one of sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfonate (SDS), potassium disproportionated rosinate, sodium fatty acid, and alkylphenol polyoxyethylene ether (OP-10), preferably a mixture of potassium disproportionated rosinate and sodium fatty acid; and / or,
[0047] The electrolyte can be a commonly used electrolyte in the rubber industry, preferably at least one of potassium phosphate, potassium chloride, and sodium bicarbonate, with potassium chloride being the most preferred; and / or,
[0048] The activator can be a commonly used activator in the rubber industry, preferably at least one of sodium formaldehyde sulfoxylate, ferrous sulfate, ferric sodium ethylenediaminetetraacetate, and tetrasodium ethylenediaminetetraacetate, and more preferably at least one of sodium formaldehyde sulfoxylate, ferrous sulfate, and tetrasodium ethylenediaminetetraacetate; and / or,
[0049] The chain transfer agent is at least one selected from n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol, carbon tetrabromide, and isooctyl 3-mercaptopropionate. The addition of a special chain transfer agent with a large chain transfer constant is to adjust the molecular weight of the rubber product. The chain transfer agent becomes a free radical through a chain transfer reaction, which can initiate the reaction, acting as an active center, and is ultimately bound to the polymer and consumed. A small amount can effectively interfere with excessive growth and branching of macromolecular chains, reducing gelation; and / or...
[0050] The initiator can be a commonly used initiator in the rubber industry, preferably at least one of p-menthol peroxide, azobisisobutyronitrile, tert-butyl hydroperoxide, and cumene hydroperoxide, more preferably at least one of p-menthol peroxide or cumene hydroperoxide; and / or,
[0051] The flocculant can be a commonly used flocculant in the rubber industry, preferably at least one of methanol, ethanol, calcium chloride, sodium chloride, dicyandiamine formaldehyde condensate, epoxide amine compounds, and dilute sulfuric acid, preferably at least one of ethanol or epoxide amine compounds.
[0052] A second objective of this invention is to provide a method for preparing itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, the method comprising:
[0053] The bio-based rubber is prepared by mixing water-soluble and oil-soluble components, adding conjugated diene monomers for pre-emulsification, adding an initiator for polymerization, and then demulsifying and drying with a flocculant.
[0054] The water-soluble components include deionized water, emulsifier, electrolyte, and activator;
[0055] The oil-soluble component includes itaconic acid ester monomers, terpene monomers, and chain transfer agents, or the oil-soluble component includes itaconic acid ester monomers, terpene monomers, chain transfer agents, and functionalized monomers.
[0056] Preferably, the pre-emulsification time is 1-5 hours, more preferably 1-2 hours;
[0057] The polymerization temperature is 0-85℃, preferably 5-75℃, and the polymerization time is 2-48h, preferably 4-24h.
[0058] The following solutions can be adopted:
[0059] First, water-soluble components are added to the polymerization reactor, followed by oil-soluble components and mixed. Then, conjugated diene monomers are added and pre-emulsified. Finally, an initiator is added to polymerize and obtain itaconic acid ester / conjugated diene / terpene multi-component copolymer latex. The latex is then demulsified with a flocculant and dried to obtain the bio-based rubber.
[0060] The water-soluble components include deionized water, emulsifiers, electrolytes, and activators.
[0061] The oil-soluble component includes itaconic acid ester monomers, terpene monomers, and chain transfer agents, or the oil-soluble component includes itaconic acid ester monomers, terpene monomers, chain transfer agents, and functionalized monomers.
[0062] A third objective of this invention is to provide a vulcanizate made from itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, wherein the vulcanizate is obtained by mixing and vulcanizing raw materials comprising the following components:
[0063] Bio-based rubber, fillers and additives.
[0064] Preferably, the filler is 10-80 parts by weight, based on 100 parts by weight of bio-based rubber;
[0065] The filler is a nanofiller, preferably silica or carbon black.
[0066] The fourth objective of this invention is to provide a method for preparing a vulcanizate made from itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber, the method comprising:
[0067] The components are mixed and then vulcanized to obtain the vulcanized rubber.
[0068] Preferably, the vulcanization is compression molding vulcanization, and the compression molding vulcanization temperature is 120-180℃.
[0069] The following solutions can be adopted:
[0070] The bio-based rubber is blended with additives and then subjected to compression molding and vulcanization at 120-180°C to obtain the vulcanized rubber.
[0071] Preferably, the additive is a commonly used additive in the rubber industry, and preferably at least one of zinc oxide, stearic acid, antioxidant 4020, antioxidant RD, accelerator CZ, accelerator NS, and sulfur;
[0072] Preferably, the mass ratio of the bio-based rubber to the additives is 100:(8-15).
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] The itaconic acid ester monomer used in this invention is derived from the bulk bio-based chemical itaconic acid, and the terpene monomer used is also derived from biomass resources, with wide applications in industrial production. The itaconic acid ester / conjugated diene / terpene multi-component copolymer is prepared using redox emulsion polymerization technology, which is environmentally friendly and has low energy consumption. The process is simple and suitable for industrial production. The resulting bio-based rubber has a molecular weight between 100,000 and 800,000, with a molecular weight distribution between 2.0 and 5.0. The prepared bio-based rubber can be processed and molded using traditional rubber processing techniques, exhibiting excellent mechanical properties. Furthermore, the large difference in glass transition temperatures between the itaconic acid ester monomer and the terpene monomer allows for a wide and adjustable glass transition temperature range after copolymerization, meeting the engineering applications of rubber. Compared to itaconic acid ester / butadiene copolymer-type bio-based engineering rubbers, this invention, by partially replacing some conjugated diene monomers with terpene monomers on the itaconic acid ester rubber structure, increases the bio-based content without sacrificing mechanical properties. Simultaneously, it significantly improves the dynamic mechanical properties of the material, resulting in a higher bio-based content, which is beneficial for the development of low-carbon rubber materials. Furthermore, the long side groups of the terpene monomers facilitate the dispersion of silica in the rubber matrix, improving the rubber's wet skid resistance while reducing its rolling resistance. The presence of functionalized monomers further enhances the interfacial interaction between the filler and the rubber. Through rational structural design, the comprehensive performance of the itaconic acid ester / conjugated diene / terpene multi-component copolymer-type bio-based rubber is comparable to that of functionalized solution-polymerized styrene-butadiene rubber (SSBR). This type of bio-based rubber molecular structure, combining high bio-based content with high performance, has not been previously reported. Attached Figure Description
[0075] Figure 1 The nuclear magnetic resonance spectrum of the bio-based rubber prepared in Example 1 of this invention;
[0076] In the figure, the chemical shift at 5.5 ppm is the single hydrogen atom bonded to a carbon atom in -CH=CH2, labeled q; the chemical shifts at 5.4–5.3 ppm are the hydrogen atom shifts of the cis-trans 1,4 double bond in butadiene, labeled h, i, l, m; the chemical shifts at 5.1–5.0 ppm are the hydrogen atom shifts of the double bond in myrcene, labeled b', f', i'; the chemical shift at 4.9 ppm is the hydrogen atom shift of the double bond in 1,2-butadiene, labeled r; the chemical shifts at 4.1–4.0 ppm are the hydrogen atom shifts of the hydrogen atom bonded to the ester group in dibutyl itaconic acid, labeled c; and the chemical shifts at 4.4 and 3.8 ppm are the hydrogen atom shifts of the hydrogen atom bonded to the ester group in glycidyl methacrylate, labeled u. The 1H NMR spectrum confirms the successful copolymerization of each monomer unit. Detailed Implementation
[0077] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0078] All raw materials used in the embodiments of this invention are commercially available products, and the specific information is shown in Table 1 below.
[0079] Table 1
[0080] Raw materials and reagents Product Description dibutyl itaconic acid Analytical grade, Sigma-Aldrich Dimethyl itaconic acid Analytical grade, Alfa Aesar diethyl itaconic acid Analytical purity, TCI Corporation Dihexyl itaconic acid Analytical purity, TCI Corporation Itaconic acid didecyl ester Analytical purity, TCI Corporation Myrcene Analytical grade, Alfa Aesar ocimene Analytical grade, Alfa Aesar Farnesene Analytical grade, Alfa Aesar butadiene Analytical grade, Sigma-Aldrich glycidyl methacrylate Analytical grade, Sigma-Aldrich methacrylic acid Analytical grade, Sigma-Aldrich Hydroxyethyl methacrylate Analytical grade, Sigma-Aldrich Acrylamide Analytical grade, Sigma-Aldrich Potassium disproportionate 50% aqueous solution, Beijing Leiberhes Biotechnology Co., Ltd. Sodium fatty acids Beijing Leiberhes Biotechnology Co., Ltd. Ferrous sulfate Analytical grade, Sigma-Aldrich Sodium formaldehyde bisulfite Analytical grade, Sigma-Aldrich Tetrasodium ethylenediaminetetraacetate Analytical grade, Sigma-Aldrich tert-dodecyl mercaptan Analytical grade, Alfa Aesar Hydrogen peroxide for monane Analytical grade, Sigma-Aldrich Potassium chloride Analytical grade, Sigma-Aldrich Deionized water Analytical grade, Beijing Chemical Plant ethanol Analytical grade, Beijing Chemical Plant
[0081] Example 1
[0082] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 40g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratio in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57.5 wt%, butadiene (x+y+z) accounts for 31 wt%, myrcene (a+b) accounts for 9 wt%, and glycidyl methacrylate (p) accounts for 2.5 wt%. Its molecular weight is 388,000 and its dispersion index is 2.9.
[0083]
[0084] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0085] Example 2
[0086] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57 wt%, butadiene (x+y+z) accounts for 22 wt%, myrcene (a+b) accounts for 17.8 wt%, and glycidyl methacrylate (p) accounts for 3.2 wt%. Its molecular weight is 358,000 and its dispersion index is 2.7.
[0087]
[0088] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0089] Example 3
[0090] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 120g myrcene were added to seal the reactor. 12g glycidyl methacrylate was added and the reactor was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 40g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 56 wt%, butadiene (x+y+z) accounts for 12 wt%, myrcene (a+b) accounts for 29.4 wt%, and glycidyl methacrylate (p) accounts for 2.6 wt%. Its molecular weight is 308,000 and its dispersion index is 2.4.
[0091]
[0092] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0093] Example 4
[0094] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 80g ocimene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / ocimene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 56.8 wt%, butadiene (x+y+z) accounts for 22.5 wt%, ocimene (a) accounts for 17.4 wt%, and glycidyl methacrylate (p) accounts for 3.3 wt%. Its molecular weight is 338,000 and its dispersion index is 2.3.
[0095]
[0096] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0097] Example 5
[0098] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 80g farnesene were added to seal the reactor. 12g glycidyl methacrylate was added and the reactor was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / farnesene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57 wt%, butadiene (x+y+z) accounts for 22.8 wt%, farnesene (a+b) accounts for 17.1 wt%, and glycidyl methacrylate (p) accounts for 3.1 wt%. Its molecular weight is 287,000 and its dispersion index is 2.5.
[0099]
[0100] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0101] Example 6
[0102] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dimethyl itaconic acid, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dimethyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dimethyl itaconic acid (n) accounts for 58 wt%, butadiene (x+y+z) accounts for 20.5 wt%, myrcene (a+b) accounts for 18.2 wt%, and glycidyl methacrylate (p) accounts for 3.3 wt%. Its molecular weight is 345,000 and its dispersion index is 2.5.
[0103]
[0104] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0105] Example 7
[0106] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g diethyl itaconic acid, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a diethyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: diethyl itaconic acid (n) accounts for 59 wt%, butadiene (x+y+z) accounts for 19.5 wt%, myrcene (a+b) accounts for 18.7 wt%, and glycidyl methacrylate (p) accounts for 2.8 wt%. Its molecular weight is 423,000 and its dispersion index is 2.6.
[0107]
[0108] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0109] Example 8
[0110] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dihexyl itaconic acid, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dihexyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dihexyl itaconic acid (n) accounts for 56.5 wt%, butadiene (x+y+z) accounts for 22.5 wt%, myrcene (a+b) accounts for 18.3 wt%, and glycidyl methacrylate (p) accounts for 2.7 wt%. Its molecular weight is 259,000 and its dispersion index is 2.7.
[0111]
[0112] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0113] Example 9
[0114] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g itaconic acid didecyl ester, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a itaconic acid didecyl ester / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: itaconic acid didecyl ester (n) accounts for 58.6 wt%, butadiene (x+y+z) accounts for 21.2 wt%, myrcene (a+b) accounts for 17.2 wt%, and glycidyl methacrylate (p) accounts for 3.0 wt%. Its molecular weight is 186,000 and its dispersion index is 3.5.
[0115]
[0116] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0117] Example 10
[0118] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 40g myrcene were added to a reaction vessel to seal the vessel. 12g methacrylic acid was added and replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / methacrylic acid bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratio in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57.8 wt%, butadiene (x+y+z) accounts for 31 wt%, myrcene (a+b) accounts for 9 wt%, and methacrylic acid (p) accounts for 2.2 wt%. Its molecular weight is 365,000 and its dispersion index is 3.0.
[0119] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0120]
[0121] Example 11
[0122] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 40g myrcene were added to a reaction vessel to seal the vessel. 12g hydroxyethyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / hydroxyethyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57.8 wt%, butadiene (x+y+z) accounts for 31 wt%, myrcene (a+b) accounts for 9 wt%, and hydroxyethyl methacrylate (p) accounts for 2.2 wt%. Its molecular weight is 288,000 and its dispersion index is 3.8.
[0123]
[0124] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0125] Example 12
[0126] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 40g myrcene were added to a reaction vessel to seal the vessel. 12g acrylamide was added and replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / acrylamide bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 57.5 wt%, butadiene (x+y+z) accounts for 31 wt%, myrcene (a+b) accounts for 9 wt%, and acrylamide (p) accounts for 2.5 wt%. Its molecular weight is 267,000 and its dispersion index is 3.3.
[0127]
[0128] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0129] Example 13
[0130] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 80g dibutyl itaconic acid, and 200g myrcene were added to a reaction vessel for sealing. 12g glycidyl methacrylate was added and replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 18.5 wt%, butadiene (x+y+z) accounts for 30.5 wt%, myrcene (a+b) accounts for 48 wt%, and glycidyl methacrylate (p) accounts for 3.0 wt%. Its molecular weight is 195,000 and its dispersion index is 3.1.
[0131]
[0132] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0133] Example 14
[0134] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 80g myrcene were added to a reaction vessel to seal the vessel. 12g glycidyl methacrylate was added and the mixture was replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g isoprene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / isoprene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 59 wt%, isoprene (x+y) accounts for 20.5 wt%, myrcene (a+b) accounts for 17.5 wt%, and glycidyl methacrylate (p) accounts for 3.0 wt%. Its molecular weight is 226,000 and its dispersion index is 2.8.
[0135]
[0136] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0137] Example 15
[0138] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 80g myrcene were added to a reactor. The reactor was then sealed and replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 80g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was then dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratio in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 60.5 wt%, butadiene (x+y+z) accounts for 21.5 wt%, and myrcene (a+b) accounts for 18 wt%, with a molecular weight of 269,000 and a dispersion index of 2.8.
[0139]
[0140] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0141] Example 16
[0142] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 40g myrcene were added to a reaction vessel for sealing. 100g glycidyl methacrylate was added and replaced with a nitrogen atmosphere (nitrogen was evacuated three times to remove oxygen). 120g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / myrcene / glycidyl methacrylate bio-based rubber (specific structure as follows). Analysis of the characteristic peak area ratios in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 46.5 wt%, butadiene (x+y+z) accounts for 20.8 wt%, myrcene (a+b) accounts for 8.2 wt%, and glycidyl methacrylate (p) accounts for 24.5 wt%. Its molecular weight is 178,000 and its dispersion index is 1.6.
[0143]
[0144] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0145] Comparative Example 1
[0146] 30g of potassium disproportionated rosinate, 10g of sodium fatty acid, 800g of deionized water, 0.1g of ferrous sulfate, 0.3g of sodium formaldehyde sulfoxylate, 0.5g of tetrasodium ethylenediaminetetraacetate, 4g of potassium chloride, 0.6g of tert-dodecyl mercaptan, and 240g of dibutyl itaconic acid were added to a reactor. The reactor was sealed and purged with nitrogen. 160g of butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g of hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g of ethanol. The latex was dried to constant weight in a vacuum oven to obtain a dibutyl itaconic acid / butadiene bio-based rubber. Analysis of the characteristic peak area ratio in the NMR spectrum showed that dibutyl itaconic acid (n) accounted for 61 wt%, and butadiene (x+y+z) accounted for 39 wt%. The molecular weight was 248,000, and the dispersion index was 2.6.
[0147]
[0148] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0149] Comparative Example 2
[0150] 30g potassium disproportionated rosinate, 10g sodium fatty acid, 800g deionized water, 0.1g ferrous sulfate, 0.3g sodium formaldehyde sulfoxylate, 0.5g tetrasodium ethylenediaminetetraacetate, 4g potassium chloride, 0.6g tert-dodecyl mercaptan, 240g dibutyl itaconic acid, and 12g glycidyl methacrylate were added to a reactor. The reactor was sealed and replaced with a nitrogen atmosphere. 160g butadiene was added, and the mixture was pre-emulsified at 25°C for 1 hour. 0.6g hydrogen peroxide was added to p-menthol to initiate polymerization, and the reaction was carried out at 10°C for 8 hours to obtain a copolymer latex. Butadiene was removed under reduced pressure, and the latex was demulsified with 500g ethanol. The latex was dried in a vacuum oven to constant weight to obtain a dibutyl itaconic acid / butadiene / glycidyl methacrylate bio-based rubber. Analysis of the characteristic peak area ratio in the NMR spectrum shows that: dibutyl itaconic acid (n) accounts for 59 wt%, butadiene (x+y+z) accounts for 38.2 wt%, and glycidyl methacrylate (p) accounts for 2.8 wt%. Its molecular weight is 326,000 and its dispersion index is 2.7.
[0151]
[0152] 100.0g of the above-mentioned bio-based rubber, 5.0g of zinc oxide, 2.0g of stearic acid, 1.0g of antioxidant 4020, 1.0g of antioxidant RD, 1.0g of accelerator CZ, 1.2g of accelerator NS, 1.5g of sulfur, 60.0g of silica 1165, and 6.0g of Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare a vulcanized rubber.
[0153] Comparative Example 3
[0154] 100.0g NR (smoked sheet rubber), 5.0g zinc oxide, 2.0g stearic acid, 1.0g antioxidant 4020, 1.0g antioxidant RD, 1.0g accelerator CZ, 1.2g accelerator NS, 1.5g sulfur, 60.0g silica 1165, and 6.0g Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150°C to prepare NR / silica vulcanizate.
[0155] Comparative Example 4
[0156] 100.0g ESBR (smoked sheet rubber), 5.0g zinc oxide, 2.0g stearic acid, 1.0g antioxidant 4020, 1.0g antioxidant RD, 1.0g accelerator CZ, 1.2g accelerator NS, 1.5g sulfur, 60.0g silica 1165, and 6.0g Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150℃ to prepare NR / silica vulcanizate.
[0157] Comparative Example 5
[0158] 100.0g SSBR (smoked sheet rubber), 5.0g zinc oxide, 2.0g stearic acid, 1.0g antioxidant 4020, 1.0g antioxidant RD, 1.0g accelerator CZ, 1.2g accelerator NS, 1.5g sulfur, 60.0g silica 1165, and 6.0g Si69 were mixed evenly on a two-roll mill to obtain a compound. The compound was then molded and vulcanized at 150℃ to prepare NR / silica vulcanizate.
[0159] The samples prepared in the above embodiments and comparative examples were subjected to performance tests. The tensile strength, tensile test at constant elongation stress (300%), and elongation at break were tested in accordance with GB / T 528-2009 standard.
[0160] According to the literature Composites Part B: Engineering, 2023, 248, 110383, the relationship between the loss factor (tanδ) and temperature was tested by dynamic viscoelastic spectrometry. The mode was tensile, and the test conditions were: 10 Hz, 0.3% strain, and heating from -80℃ to 100℃ at 3℃ / min.
[0161] The specific test results are shown in Table 2 below:
[0162] Table 2
[0163]
[0164] Note: Since the elongation at break of some embodiments and comparative examples did not reach 300%, the 300% constant elongation strength in the table did not yield corresponding results.
[0165] For rubber composites used in tire treads, a larger tanδ value at 0℃ indicates better wet skid resistance and improved braking safety in tires made from this material; a smaller tanδ value at 60℃ indicates lower rolling resistance and better fuel economy in tires made from this material. Table 2 shows that the mechanical and dynamic mechanical properties of the itaconic acid ester / conjugated diene / terpene multi-component copolymer composite prepared in this invention can be controlled by the itaconic acid ester side group length and the terpene monomer feeding ratio. Specifically, the introduction of terpene units significantly improves wet skid resistance and reduces rolling resistance, improving both properties simultaneously. However, excessive terpene monomer introduction can lead to a loss of mechanical properties, so an appropriate amount should be selected. Furthermore, as the itaconic acid ester side group length decreases, its wet skid resistance improves, but rolling resistance increases accordingly. Based on this control relationship, selecting appropriate side group length and terpene feeding amount can regulate the dynamic mechanical properties of the composite material.
[0166] Compared with Comparative Examples 1 and 2, the bio-based rubber prepared in this embodiment of the invention exhibits significantly improved dynamic mechanical properties. While its mechanical properties are slightly inferior to NR and ESBR, its wet skid resistance and rolling resistance are significantly better, and its overall performance is comparable to SSBR. This indicates that the bio-based rubber structure provided in this study not only has a higher bio-based content but also possesses both high wet skid resistance and low rolling resistance, providing insights for the design of next-generation novel bio-based rubbers for tire treads.
[0167] In addition, bio-based rubber materials with low mechanical properties but high bio-based content can also be used in applications such as low-carbon shoe soles.
[0168] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications are possible without departing from the technical solutions described in the claims.
Claims
1. A bio-based rubber of itaconic acid ester / conjugated diene / terpene multi-component copolymer, characterized in that... The structural formula of the bio-based rubber is: n' is 1-5, and R1 and R2 are hydrogen atoms or carbon atoms. 1~20 The alkyl group, a+b = 1-90%, n = 1-99%, x+y+z = 1-95%, p = 0-30%, X1 is a hydrogen atom or a methyl group, and X2 is a functional group structure containing at least one of an epoxy group, a carboxyl group, a hydroxyl group or an amide group, wherein R1 and R2 are the same or different.
2. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 1, characterized in that: n' is 2 or 3, R1 is hydrogen or C 1-10 Alkyl group, where R2 is hydrogen or C 1-10 Alkyl groups, a+b = 5-70%, n = 10-90%, x+y+z = 5-90%, p = 0-10%.
3. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 1, characterized in that: The bio-based rubber has a number-average molecular weight of 50,000 to 1,000,000 and a molecular weight distribution of 1.5 to 10.
0.
4. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 3, characterized in that: The bio-based rubber has a number-average molecular weight of 100,000 to 800,000 and a molecular weight distribution of 2.0 to 5.
0.
5. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 1, characterized in that... The bio-based rubber is obtained by copolymerizing raw materials comprising the following components: Each component, by weight: Based on a total weight of 100 parts by weight of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer: The mass ratio of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer is (0.14–18):(0.07–18):1; 0-30 parts by weight of functionalized monomers; 100-300 parts by weight of deionized water; Emulsifier 0.1-15 parts by weight; Electrolyte 0.1-3 parts by weight; Activator: 0.01-0.2 parts by weight; Chain transfer agent 0.01-0.4 parts by weight; Initiator 0.01-5 parts by weight; The amount of flocculant used is 20-60 wt% of the total weight of the copolymer latex after polymerization.
6. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 5, characterized in that: Each component, by weight: Based on a total weight of 100 parts by weight of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer: The mass ratio of itaconic acid ester monomer, conjugated diene monomer, and terpene monomer is (0.16–16):(0.08–16):1; Functionalized monomers: 0-10 parts by weight; 150-250 parts by weight of deionized water; Emulsifier 2-10 parts by weight; Electrolyte 0.1-1.5 parts by weight; Activator: 0.02-0.1 parts by weight; Chain transfer agent 0.03-0.25 parts by weight; Initiator 0.02-2 parts by weight; The amount of flocculant used is 30-50 wt% of the total weight of the copolymer latex after polymerization.
7. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 5, characterized in that: The structural formula of the itaconic acid ester monomer is: R1 and R2 are hydrogen atoms or C atoms. 1~20 Alkyl groups, wherein R1 and R2 may be the same or different; and / or, The conjugated diene monomer is C n H 2n-2 At least one of the following, where n≥4; and / or, The terpene monomer is (C5H8). n At least one of them, where n≥1; and / or, The functionalized monomer is at least one selected from glycidyl methacrylate, methacrylic acid, hydroxyethyl methacrylate, acrylamide, and vinyl acetate; and / or, The emulsifier is at least one selected from sodium dodecylbenzenesulfonate, sodium dodecyl sulfonate, potassium disproportionated rosinate, sodium fatty acid, and alkylphenol polyoxyethylene ether; and / or The electrolyte is at least one selected from potassium phosphate, potassium chloride, and sodium bicarbonate; and / or, The activator is at least one selected from sodium formaldehyde sulfoxylate, ferrous sulfate, ferric sodium ethylenediaminetetraacetate, and tetrasodium ethylenediaminetetraacetate; and / or, The chain transfer agent is at least one selected from n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol, carbon tetrabromide, and isooctyl 3-mercaptopropionate; and / or, The initiator is at least one selected from p-menthol peroxide, azobisisobutyronitrile, tert-butyl hydroperoxide, and cumene hydroperoxide; and / or... The flocculant is at least one of methanol, ethanol, calcium chloride, sodium chloride, dicyandiamine-formaldehyde condensate, epoxy amine compounds, and dilute sulfuric acid.
8. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 7, characterized in that: R1 is hydrogen or C. 1-10 Alkyl group, where R2 is hydrogen or C 1-10 Alkyl groups.
9. The itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 7, characterized in that: The itaconic acid ester monomer is at least one selected from the following: dimethyl itaconic acid, monomethyl itaconic acid, diethyl itaconic acid, monoethyl itaconic acid, dipropyl itaconic acid, monopropyl itaconic acid, dibutyl itaconic acid, monobutyl itaconic acid, dipentyl itaconic acid, monopentyl itaconic acid, dihexyl itaconic acid, diheptyl itaconic acid, monoheptyl itaconic acid, dioctyl itaconic acid, dinonyl itaconic acid, monononyl itaconic acid, didecyl itaconic acid, and monodecyl itaconic acid; and / or, The conjugated diene monomer is at least one of C4H6 or C5H8; and / or The terpene monomer is at least one of (C5H8)2 or (C5H8)3; and / or, The emulsifier is a mixture of potassium disproportionated rosinate and sodium fatty acid; and / or, The electrolyte is potassium chloride; and / or, The activator is at least one selected from sodium formaldehyde sulfoxylate, ferrous sulfate, and tetrasodium ethylenediaminetetraacetate; and / or, The initiator is at least one of p-monane hydrogen peroxide or dicumyl peroxide; and / or The flocculant is at least one of ethanol or epoxide amine compounds.
10. A method for preparing an itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber as described in any one of claims 1-9, characterized in that... The method includes: The bio-based rubber is prepared by mixing water-soluble and oil-soluble components, adding conjugated diene monomers for pre-emulsification, adding an initiator for polymerization, and then demulsifying and drying with a flocculant. The water-soluble components include deionized water, emulsifier, electrolyte, and activator; The oil-soluble component includes itaconic acid ester monomers, terpene monomers, and chain transfer agents, or the oil-soluble component includes itaconic acid ester monomers, terpene monomers, chain transfer agents, and functionalized monomers.
11. The method for preparing itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 10, characterized in that: The pre-emulsification time is 1-5 hours; The polymerization temperature is 0-85℃, and the polymerization time is 2-48h.
12. The method for preparing itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 11, characterized in that: The pre-emulsification time is 1-2 hours; The polymerization temperature is 5-75℃, and the polymerization time is 4-24h.
13. A vulcanizate made from the itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to any one of claims 1-9, characterized in that... The vulcanized rubber is obtained by mixing and vulcanizing raw materials comprising the following components: Bio-based rubber, fillers and additives.
14. A method for preparing a vulcanizate made from itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber as described in claim 13, characterized in that... The method includes: The components are mixed and then vulcanized to obtain the vulcanized rubber.
15. The method for preparing the vulcanizate from itaconic acid ester / conjugated diene / terpene multi-component copolymer bio-based rubber according to claim 14, characterized in that: The vulcanization is compression molding vulcanization, and the compression molding vulcanization temperature is 120-180℃.
Citation Information
Patent Citations
Method for preparing itaconic ester / isoprene copolymer type bio-based engineering elastomer through low temperature emulsion polymerization
CN102558437A
Itaconate / butadiene copolymer type bioengineering rubber and preparation method thereof
CN104945817A